Attitudes to psychiatry and to mental illness among nursing students: Adaptation and use of two validated instruments in preclinical education. Issue 3 (27th December 2019) - Martin, Andrés; Krause, Robert; Chilton, Julie; Jacobs, Asaf; Amsalem, Doron
Accessible Summary: What is known on the subject: Stigma towards psychiatry and people with serious mental illness (SMI) is prevalent among healthcare providers and can adversely affect patient care. Internalized stigma among nurses can affect personal self‐care and limit help‐seeking behaviours. Stigma around mental health nursing can adversely affect recruitment into this already underserved field. What the paper adds to existing knowledge: This is the first report on the adaptation and use in a nursing student sample of two widely used stigma‐related instruments that have been normed among medical students. The attitudes to psychiatry (ATP‐30) and the attitudes to mental illness (AMI) instruments proved sensitive to change and can be useful in tracking specific anti‐stigma curricular interventions. Interactive and participatory student activities in courses such as ours (that include simulation with standardized patients, clinical placements and patient interaction) need to be complemented by exposure to individuals with lived experience with mental illness in order to address stigmatized views of SMI. Nursing educators and fellow nurses willing to share their own experiences with mental illness—including diagnosis, health–seeking, treatment and recovery—may prove especially powerful and germane during nursing school. What are the implications for practice: Even a strong academic curriculum is not sufficient to change stigmatized perceptions about mental illness, psychiatric care and mental health nursing as a profession. Comparison and potential synergy between ATP‐30, AMI and OMS‐HC (Opening Minds Scale for Health Care Providers) could prove fruitful in identifying a more comprehensive approach to stigma assessment over time. The addition of validated instruments, such as the Self‐Compassion Scale–Short Form (SCS–SF) and the Self‐Stigma of Seeking Help (SSOSH), which tap into internalized stigma and into health‐seeking behaviours and intervening barriers could prove particularly useful in evaluating innovative interventions for stigma‐decreasing initiatives in nursing education. Interactive and participatory didactic offerings need to be complemented by exposure to individuals with lived experience with mental illness and ideally to nursing educators and practicing nurses willing to share their histories of diagnosis, help‐seeking, treatment and recovery. Abstract: Introduction: Stigma towards psychiatry and to people with serious mental illness (SMI) is prevalent among healthcare providers and can adversely affect patient care. Such stigmatized views can adversely affect recruitment into the already underserved field of mental health nursing. Aim/question: We adapted two stigma‐related instruments in a sample of nursing students and examined change in scores after participation in an eight‐week preclinical psychiatry curriculum. Our goal was to identify stigma‐malleable opportunities that would inform refinements in future iterations of a preclinical psychiatry curriculum in nursing. Method: We made minor adaptations to the attitudes to psychiatry (ATP‐30) and the attitudes to mental illness (AMI) instruments. We invited first‐year nursing students to complete assessments at two time points: before and after completion of an eight‐week core course in preclinical psychiatry. Results: Seventy‐one students completed the assessment at both time points. ATP‐30 and three of its eight subscale scores improved by course's endpoint. By contrast, AMI scores did not change. Compared with medical student published norms, nursing students in our sample had higher (less stigmatized) average scores. Discussion: The ATP‐30 and the AMI can be easily adapted to a nursing student population and may prove useful in tracking specific anti‐stigma educational interventions. Implications for practice: A general psychiatry course during nursing school is, it and of itself, unlikely to change biased views about SMI and should be enhanced with exposure to, and interaction with individuals with lived experiences of mental illness, ideally by nurse educators and practicing nurses.